A double-hit of stress and low-grade inflammation on functional brain network mediates posttraumatic stress symptoms - Jungyoon Kim (Nature Portfolio, 2020)
Low-grade systemic inflammation and stress increase vulnerability to neuropsychiatric disorders. Here, the authors show that inflammation and stress-induced changes in higher order cognitive networks increase vulnerability to posttraumatic stress disorder.